MULTI UNIT ABUTMENTS RECOMMENDED IN PROSTHETIC AND SURGICAL IMPLANTOLOGY TREATMENT (CASE REPORT) - Janev, Edvard Jordan; Redzep, Enis; Janeva, Nadica; Mindova, Sonja (Journal of Morphological Sciences, 2020)
Possibility for choosing multi-unit abutments in oral implantology create prosthetic flexibility on implant supported restorations. Multi-unit abutments offer a level of predictable esthetics, with consistent fit and function, that has greatly improved the effectiveness of implant supported constructions. The aim of this study is to show proven and documented clinical efficacy of multi-unit abutments, cost-effective solutions and portfolio of prosthetic restorations as one of the most comprehensive available. A case of a 45-year old patient with partial edentulous maxilla and previously prosthodontic treatment failure is presented. The clinical and paraclinical examination showed that the limited edentulous spaces were marginally acceptable for implant supported restorations. Combination of multi-unit abutments and definitive prosthetic construction were delivered six months after implant osseointegration.   Keywords:abutments, dental implants, restorations, prosthodontic treatment, esthetic.